Quality of "pandawa" services at the Sukabumi branch of the Health Social Security Agency 2020-2023 - Qori Febriyanti; Rizki Hegia Sampurna; Tuah Nur (Publisia: Jurnal Ilmu Administrasi Publik, 2025)
This research aims to analyze the quality of service from the Pandawa Service (Pelayanan Administrasi Melalui Whatsapp) at the Sukabumi Branch of the Health Social Security Agency in 2020-2023. The Pandawa service is an innovative strategy developed by BPJS Health that aims to reduce the number of participants who come to the BPJS office to prevent the spread of COVID-19. However, the transfer services have yet to be able to reduce the number of visits to the BPJS Health Sukabumi City Branch office. The method used is a qualitative method with a descriptive approach. Determination of informant’s technique snowball sampling. This research uses the theory of Parasuraman et al. (1988). Data collection techniques include observation, interviews, documentation and audio-visual material. The research results show that the quality of Pandawa services is running quite well. However, this is not yet optimal due to a lack of understanding and response from the community and participants regarding the socialization that has been carried out; some services are not accommodated through Pandawa and require the community and participants to come directly to the BPJS Health Sukabumi Branch office.